Sensitive Objects: Affect and Material Culture - Povrzanovic Frykman, Maja; Frykman, Jonas (Kriterium, 2016)
"The study of affect has become a dynamic field spanning a range of disciplines from psychology over neuroscience to philosophy and cultural studies. Little attention however has been payed to material culture. This book presents an innovative set of ethnographies of the affective relations between people and things. It tackles the sensual experiences of materiality, through taste, sounds, smells and touch that are hard to verbalize or represent in images. Evocative situations are detailed, like for instance the packing of a suitcase at the splitting of a marriage; how people in the besieged Sarajevo were both helped and humiliated by the aid received from abroad; how the parting of objects after the parents' death may result in siblings never talking to one another again. These ethnographies from Scandinavia, the Balkans and the US, focus on what affects do in everyday life rather than what they are. The volume is also provided with chapters that put the studies of affects in ethnology and anthropology in a wider scholarly frame and discuss theories and methods applied in the book. Sensitive Objects in the first place addresses scholars and students in Ethnology, Anthropology, Sociology and Cultural Studies, as well as other readers interested in affects and emotions, material culture, tourism, innovations, and post-socialism.